2002
DOI: 10.1098/rspb.2002.2065
|View full text |Cite
|
Sign up to set email alerts
|

Positive fitness consequences of interspecific interaction with a potential competitor

Abstract: The coexistence of species sharing mutual resources is usually thought to be limited by negative processes such as interspecific competition. This is because an overlap in resource use leads to negative fitness consequences, and traits favouring avoidance of potential competitors, for example in habitat selection, are therefore selected for. However, species interactions are acknowledged to vary from negative (competition) to mutualism, although empirical evidence for positive interspecific interactions from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 41 publications
8
177
1
Order By: Relevance
“…Social information has been shown to play a critical role for habitat quality assessment and settlement decisions in the Ficedula species. Flycatchers use both conspecific and heterospecific density, reproductive investment, or success for breeding habitat selection and adjustment of reproductive effort (Doligez et al, 1999(Doligez et al, , 2002(Doligez et al, , 2004aForsman et al, , 2012, which results in fitness benefits (Forsman et al, 2002). Experiments have also shown that flycatchers copy the (apparent) nest site preference of their main heterospecific competitors, great tits Parus major and blue tits Cyanistes caeruleus Seppänen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social information has been shown to play a critical role for habitat quality assessment and settlement decisions in the Ficedula species. Flycatchers use both conspecific and heterospecific density, reproductive investment, or success for breeding habitat selection and adjustment of reproductive effort (Doligez et al, 1999(Doligez et al, , 2002(Doligez et al, , 2004aForsman et al, , 2012, which results in fitness benefits (Forsman et al, 2002). Experiments have also shown that flycatchers copy the (apparent) nest site preference of their main heterospecific competitors, great tits Parus major and blue tits Cyanistes caeruleus Seppänen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of breeding site selection, social information use is expected to be highly beneficial, because acquiring the same information by direct sampling of the environment can entail high costs in terms of time, energy, and missed opportunities, especially in short-lived species (Doligez and Boulinier, 2008), and the use of social information for breeding site selection has indeed been experimentally demonstrated in different species (Doligez et al, 2002;Boulinier et al, 2008). In the flycatchers-tits system, pied flycatchers have been shown to gain fitness benefits when breeding in proximity to great tits (by achieving earlier breeding, and heavier and larger broods; Forsman et al, 2002). Flycatchers have also been observed actively prospecting inside great tit nest boxes (Forsman and Thomson, 2008;Forsman et al, in press) despite a high risk of being killed (Merilä and Wiggins, 1995).…”
Section: No Additive Genetic Variancementioning
confidence: 99%
“…This has resulted in an arms race between the two species and in an attempt to hide their eggs from prospecting flycatchers, great tits usually cover them with nesting materials whenever they leave the nest during the egg laying period in order to prevent flycatchers using them as a cue in their nest site selection decisions (Loukola et al, 2014). Nevertheless, there is widespread evidence that several species of migratory passerine birds base their settlement decisions on the settlement decisions of the resident tits (Mönkkönen et al, 1990;Forsman et al, 2002Forsman et al, , 2007Forsman et al, , 2009Forsman and Seppänen, 2011;Loukola et al, 2012Loukola et al, , 2013Jaakkonen et al, 2015). Illustratively, both the average number of species and the total density of migratory birds that chose to breed in habitat patches were positively correlated with the experimentally-varied density of titmice already breeding within those habitat patches, thereby indicating that migrants probably use titmice density as an indicator of breeding habitat quality because they share similar food resources (Forsman et al, 2009).…”
Section: Social Behaviours Over Spatial Scalesmentioning
confidence: 99%
“…In short, data from the literature (Curio 1959, Lundberg & Alatalo 1992, Sandberg 1996 were supplemented with data we collected at the Hoge Veluwe from 2003 to 2004, and data provided from a population at 64°N by J. T. Seppanen (see Forsman et al 2002). We only included data for which arrival was scored for a large proportion of the population, and for males and females separately.…”
Section: Bird Data Selection and Analysismentioning
confidence: 99%